The wheel of time the shamans of ancient Mexico, their thoughts about life, death and the universe - Castaneda, Carlos 1931-1998 (Washington Square Press, publication of Pocket Books, 2001)
Contains a selection of quotations, collected by the author from his works on his training as a shaman initiate, including "The Teachings of Don Juan," "Journey to Ixtlan," " A Separate Reality," and "Tales of Power."